Excitation wavelength-dependent multi-coloured and white-light emissive pyrene-based hydrazones: suppression of Kasha's rule - Kumar, M. Naveen; Lyngkhoi, Deikrisha Lyngdoh; Gaikwad, Sudhakar; Samanta, Jayanta; Ahamed, Rafiq; Khatua, Snehadrinarayan; Pramanik, Susnata (Chemical Communications, 2023)
Multi-coloured and white-light emissions from pyrene-based hydrazones are described. They exhibit excitation wavelength-dependent emissions in solution due to the suppression of Kasha's rule. Interestingly, in dimethylformamide, 1-3 emit light that covers all the regions of primary colours as a function of excitation wavelength, and 1 and 2 emit white light (lambda ex = 420 nm) in isopropanol. Multi-coloured and white-light emissions from pyrene-based hydrazones are described.